2005
DOI: 10.3758/bf03193793
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval-induced forgetting in implicit memory tests: The role of test awareness

Abstract: A number of studies using the retrieval-practice paradigm have shown that inhibition can play a role in retrieval from memory (for a review, see Anderson, 2003). In the retrieval-practice paradigm, participants first study a number of category-exemplar pairs, followed by retrieval practice with half of the studied exemplars from half of the studied categories. Retrieval practice is carried out using a category-plus-word-stem cued recall task. Their memory is then tested for both practiced and unpracticed exemp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 15 publications
2
43
0
Order By: Relevance
“…Finally, during the test phase, Cadburys is cued from a different product category such as 'Chocolate'. In tests of implicit memory, the independent probe technique has been used recently by Camp, Pecher, and Schmidt (2005). They found that retrieval-induced forgetting was present only for participants who were aware of the relationship between the study and test phases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, during the test phase, Cadburys is cued from a different product category such as 'Chocolate'. In tests of implicit memory, the independent probe technique has been used recently by Camp, Pecher, and Schmidt (2005). They found that retrieval-induced forgetting was present only for participants who were aware of the relationship between the study and test phases.…”
Section: Discussionmentioning
confidence: 99%
“…However, research that has made use of such measures indicates that many participants do become aware spontaneously of the study-test relationship even if not informed by the experimenter (e.g. Bowers & Schacter, 1990;Camp et al, 2005;Mulligan et al, 1999). The issue at stake here relates to the distinction between retrieval intention and awareness (Richardson-Klavehn & Gardiner, 1995;Richardson-Klavhen et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A broad base of findings supports cue independence under many conditions in both episodic and semantic memory (e.g., M. C. Anderson & Bell, 2001; M. C. Anderson, Green, & McCulloch, 2000;M. C. Anderson & Spellman, 1995;Aslan, Bäuml, & Grundgeiger, 2007;Camp, Pecher, & Schmidt, 2005;Levy, McVeigh, Marful, & Anderson, 2007;MacLeod & Saunders, 2005;Saunders & MacLeod, 2006;Shivde & Anderson, 2001; for exceptions, see Camp, Pecher, & Schmidt, 2007;Perfect et al, 2004;Williams & Zacks, 2001). Thus, retrieval often appears to induce RIF that reflects changes to the state of the competitor, consistent with inhibition.…”
Section: The Goal Of the Independent Probe Methodsmentioning
confidence: 99%
“…The nature of this influence, at present, is unclear. On the one hand, Perfect et al (2004) and Camp et al (2005) argued that covertly recalling the practiced category may trigger recall of practiced items (e.g., Orange) that would then block unpracticed items (e.g., Banana). If so, blocking could explain independent probe impairment, albeit with complex assumptions about the cues participants use.…”
Section: The Covert Cuing Hypothesis and The Cue Enhancement Effectmentioning
confidence: 99%